2007
DOI: 10.1080/01140670709510198
|View full text |Cite
|
Sign up to set email alerts
|

Response of irrigated common bean (Phaseolus vulgaris) yield to foliar zinc application in Spain

Abstract: Common bean (Phaseolus vulgaris) is susceptible to Zinc (Zn) deficiency. The objective of this study was to verify the influence of foliar application of Zn on irrigated bean yield in northwest Spain. The work was carried out during 1999 and 2001 in the province of León. The design was a split-plot design and the primary and secondary factors were, respectively, Zn dose (0, 50, and 100 g Zn/ha) and the number of Zn applications (1 or 2). Yield was increased with Zn foliar application to 20.74 g/plant at 50 g Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…However, the yield increased only up to Zn5, while Zn10 treatment caused a decrease in grain yield. Similar increase in chickpea grain yield due to Zn fertilization was reported by Brennan et al (2001) and Pathak et al (2012), which might have a link with increased number of pods per plant, as in other leguminous species (Valenciano et al, 2007). Khan (1998) reported increased grain yield mainly because of increasing pod bearing when Zn was applied in conditions of high moisture availability.…”
Section: Discussionsupporting
confidence: 61%
“…However, the yield increased only up to Zn5, while Zn10 treatment caused a decrease in grain yield. Similar increase in chickpea grain yield due to Zn fertilization was reported by Brennan et al (2001) and Pathak et al (2012), which might have a link with increased number of pods per plant, as in other leguminous species (Valenciano et al, 2007). Khan (1998) reported increased grain yield mainly because of increasing pod bearing when Zn was applied in conditions of high moisture availability.…”
Section: Discussionsupporting
confidence: 61%
“…Zn increased growth and yield (Khan et al, 2000). The increase in yield was the result of the increase in the number of pods per plant, which is the same as other leguminous plants (Valenciano et al, 2007). In a previous Zn fertilization study involving pots Khan (1998) also reported an increase in grain yield, which was mainly due to an increase in the number of pods per plant, with the application of Zn when the soil had high moisture availability.…”
Section: Discussionmentioning
confidence: 53%
“…The increased yield was the result of an increased number of pods plant -1 , as in other leguminous plants (Valenciano et al, 2007). In Zn fertilization studies using pot assays, Khan (1998) reported increased grain yield mainly by increasing pod bearing when Zn was applied in conditions of high moisture availability.…”
Section: Resumen Comunicación Corta Respuesta Del Garbanzo a Las Aplmentioning
confidence: 97%